Pembagian Harta Waris Beda Agama Menurut Hukum Islam, Hukum Perdata dan Hukum Adat - Badai Husein Hasibuan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
Choice of law in the division of the inheritance of different religions, the inheritance of different religions in Indonesia is practiced in three provisions, namely, application in Islamic law (in religious courts), application in civil law (in the court), and its application in customary law.From the discussion that took place it can be concluded that, according to Islamic law, religious differences can constitute an obstacle to inheritance, but in practice in religious courts non-Muslims inherit from their parents or relatives the estate in the form of wills. In applying the Law on Inheritance of Different Religions in Medan District Court, the Chamber of Judges in its review applied Civil Law (BW) and did not apply the provisions of Islamic Law even if one of the parties was a Muslim. According to the results of the decision of the religious courts, there is a conflict between the previous rules contained in the hadith, the consensus of the scholars and the compilation of Islamic law, which expressly states that non-Muslims do not have the right to inherit the property of Muslims. heirs due to different religions and is not expected to have a binding will as determined by the Supreme Court. If we look at the decision, it is a legal development in the interest of justice and legal certainty for today's very diverse society.